2005
DOI: 10.1002/jcu.20095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diffuse fatty infiltration of the liver on hepatic artery resistance index

Abstract: Hepatic artery resistance index decreases as the severity of diffuse fatty infiltration increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
44
1
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 12 publications
12
44
1
7
Order By: Relevance
“…Hepatomegaly is a prevalent finding in patients with NAFLD and liver size increases as the degree of NAFLD increases [3,10,15]. In our study, similar to the medical literature, we found that liver size was increased with an increase of fatty infiltration with a statistically significant difference.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Hepatomegaly is a prevalent finding in patients with NAFLD and liver size increases as the degree of NAFLD increases [3,10,15]. In our study, similar to the medical literature, we found that liver size was increased with an increase of fatty infiltration with a statistically significant difference.…”
Section: Discussionsupporting
confidence: 87%
“…Fibrosis of the liver parenchyma or fat deposition in NAFLD can affect and decrease vascular compliance and decrease the portal vein inflow [12]. To compensate the blood flow to the liver, hepatic artery diastolic flow increases and makes HARI lower than normal [10]. But Colli et al found higher HARI values in alcoholic or viral-related cirrhosis than in a control group, indicating fibrosis in the liver [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the traditional ultrasound (US) is an excellent diagnostic technique to reveal the presence of diffuse fatty liver disease, it is neither sensitive nor specific to reveal fibrosis, except in advanced stages where signs of cirrhosis are evident. Previous studies have demonstrated that hepatic artery resistive index (HARI) is significantly altered in patients with NAFLD, with significant reduction of this parameter with increasing of severity of diffuse fatty liver disease [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The liver parenchyma was scanned and vascular malformations and spaceoccupying lesions were excluded. Using B-mode sonography, the presence or absence and severity of fatty infiltration was graded using a scale from 0 to 3 as previously reported by Mihmanli et al (2005), indicating absent, mild, moderate, and severe hepatosteatosis, respectively, corresponding to increasing degrees of hepatic echogenicity with poorer visualization of the intrahepatic vessels and diaphragm. Grade 0 (control) patients had normal liver echogenicity.…”
mentioning
confidence: 99%